LEGAL PROTECTION FOR WORKERS WITH A SPECIFIC TIME WORK AGREEMENT (PKWT) VIEWED FROM A LABOR LAW PERSPECTIVE - Safitri, Nabila Nur (Jurnal Pengembangan Ketenagakerjaan, 2024)
In the labour sector, an agreement is needed as something that binds both parties between the entrepreneur or employer and the worker. Agreements can be divided into two, namely agreements with a certain time and agreements with an indefinite time. In this article, it will discuss workers with fixed-term agreements, where the rights obtained are very unequal to the rights obtained by workers with indefinite-term agreements. This concerns the obligations of entrepreneurs or employers to fulfill the rights that must be given to workers. Legal protection is needed in the agreement so that workers can get legal certainty in carrying out their actions. The method used in writing is the normative legal writing method, which is based on literature study. The results and discussion of the following article are that legal protection from the state for workers, especially workers with PKWT, is contained in Law Number 13 of 2013 concerning Manpower, Law Number 11 of 2020 concerning Job Creation, and Law Number 6 of 2023 regarding changes to Law Number 11 of 2022. Apart from the existence of legal protection for workers, there are still many violations that workers receive from entrepreneurs or employers due to several factors, including a job vacancy system that opens a fixed-term contract system as well as the impact of the 1998 economic crisis and the Covid-19 pandemic.